Improved modeling of double default effects in Basel II: an endogenous asset drop model without additional correlation - Ebert, Sebastian; Lütkebohmert, Eva (Bonn Econ Discussion Papers, 2009)
In 2005 the Internal Ratings Based (IRB) approach of "Basel II" was enhanced by a "treatment of double default effects" to account for credit risk mitigation techniques such as ordinary guarantees or credit derivatives. This paper reveals several severe problems of this approach and presents a new method to account for double default effects. This new asset drop technique canbe applied within any structural model ofportfolio credit risk. When formulated within the IRB approach of Basel II, it is very well suited for practical application as it does not pose extensive data requirements and economic capital can still be computed analytically. -- Basel II ; double default ; IRB approach ; regulatory capital ; structural credit portfolio models